Analisis Kecelakaan Kerja Pada Atlet Sepatu Roda Jawa Tengah - Ayu, Abigail Guinevere Puteri Nimas; Suroto, Suroto; Kurniawan, Bina (Jurnal Kesehatan Masyarakat, 2024)
Roller skating is a sport that is being favored by the community. This sport has a high risk of danger that can cause various injuries. This study aims to analyze work accidents in Central Java’s roller skate athletes. The type of research used is qualitative research. The research subjects were roller skaters in Central Java as the main informants and roller skate trainers in Central Java as triangulation informants. Informants were selected using purposive sampling. Data collection was carried out by in-depth interviews, observation, and documentation. The results showed that the factors that cause accidents in roller skate athletes are mostly due to collisions and slips. Potential injuries that are often experienced by roller skaters in Central Java are injuries to the ankle, knee, lower leg, upper leg, elbow, finger and wrist, waist and hip. More specifically, the types of injuries that occur are injuries such as skin abrasions, abrasions, bruises, cramps, cramps or muscle spasms, and dislocations. The conclusion is that injuries that occur are caused by falls/ slips due to collisions between athletes, the shape and condition of the track, the techniques used by athletes, and the condition of the equipment used can also determine the level of injury received.